Esophageal perforation caused by impacted hot potato successfully managed nonoperatively: A rare case report from Ethiopia and literature review - Abdi Alemayehu, MD; Irko Worku, MD; Gulilat Sisay, MD; Eyerusalem Getachew, MD; Firaol Birhanu, BSc; Desalegn Fikadu, MD (Radiology Case Reports)
Esophageal perforation represents a rare but life-threatening emergency that demands prompt diagnosis and multidisciplinary management to reduce associated morbidity and mortality. Although any esophageal segment may be affected, the thoracic esophagus is most frequently involved, with perforations typically resulting from iatrogenic causes, trauma, or spontaneous rupture. Food bolus-induced perforations are exceptionally uncommon, with perforation by impacted hot potato being extraordinarily rare—only 1 prior case has been reported in medical literature. Computed tomography (CT) plays an indispensable diagnostic role, with characteristic findings including focal esophageal wall discontinuity, extraluminal mediastinal gas, and adjacent fat stranding. We describe a 16-year-old male prisoner who presented with chest pain and dysphagia 48 hours after inadvertently swallowing a hot potato; CT confirmed thoracic esophageal perforation secondary to the impacted bolus. The patient was managed nonoperatively with excellent clinical outcome. To our knowledge, this represents only the second reported case of esophageal perforation caused by an impacted hot potato.